Perancangan Sistem Jaringan Komputer Menggunakan Teknik Failover Pada Routing Static Yang Bersifat Recursive Connection - Budi Hartanto (Jurnal Ilmiah SINUS, 2019)
In a computer network system when using more than one router that is interconnected will experience a problem in the process of sending data packets. The problem is that if the main line is disconnected, then the data packet is unable to send data to a computer network system. The purpose of this study is to make a computer network system design with fail over technique on the type of static routing that is not directly connected. In this case the researcher used the Microtub Router Board RB-951-2nd. Failover technique is a way to transfer routing paths when the main line is broken, so it can be diverted to the backup routing path, this is so that the computer network connection path continues smoothly. The researcher used a recursive network connection case or the router is not connected directly to the main point center (main gateway), so the researcher used the optimization of the Target Scope and Distance features in the Microtic Router Board. The results of this study was that the backup routing path was able to channel data packets within the network if the main line did not respond or could not be connected.